SOCIAL LOAFING: AN EXPLORATORY STUDY ON HIGH-SCHOOL STUDENTS - Nur Afif; M. Ahkam Alwi; Faradillah Firdaus (JURNAL NALAR PENDIDIKAN, 2024)
At school, students often get assignments in group form. However, in the process of working on group assignments, sometimes some students show less than optimal efforts due to the presence of other group friends. Social loafing is a tendency shown by individuals to show less than optimal effort when working in groups. This research aims to explore the background of the occurrence of social loafing in an academic context by focusing on high school (SMA) students. The exploratory study in this research used an open-ended questionnaire to collect data using analytical techniques in the form of content analysis with a mixed-method approach. The research results show that lack of contribution, excessive expectations, lack of self-awareness, and lack of self-confidence are the background for social loafing